A gestão democrática na educação do Distrito Federal - concepções e historicidade das experiências de 1957, 1995 e 2012 - Rodrigues, Rodrigo Soares Guimarães (2016)
This thesis is linked to the research line "State, Policies and History of Education" and aims to investigate the construction of democratic management in the Federal District taking as reference an initial experience experienced in the constitution of the network in 1957 and the legal milestones by means of laws 957 / 1995 and 4751/2012. Through a study of historical approach, it was sought to map and describe these conceptions of democratic management within these three moments of the public network of the Federal District, explaining possible similarities and divergences between the present formats of the 1990s and the built in experience Initial. In this movement, the thesis answered the following research questions: 1) Is it possible to visualize and point out, within the initial history and in the actuality of SEEDF, similarities between the democratic management that emerges at these three moments? 2) How is democratic management characterized in the historical times mentioned? 3) What influence do history and legislation have on the democratic management that is taking place today in the public schools of the Federal District? For the development of this research, we opted for exploratory historical research, in a qualitative perspective, aiming to investigate the documents and legislation that, in the historical course of the educational reality of the Federal District, allowed to analyze the process of construction of democratic management in this network Public. This study also allowed an analysis of the historical movement of construction of democratic management in the DF, with the initial moment of SEEDF and, in parallel with the realities of 1995 and 2012, searching for clues capable of pointing out important elements for the understanding of this process. Thus, the thesis makes explicit that DF public education plays an important role in the understanding of democratic management in Brazil, since in the first school of this network an embryo of democratic experience is registered both in its representative and participatory dimensions, Same way that, later, its manifestations also brought significant advances in this sense.